Compensating Wounded Warriors An Analysis of Injury, Labor Market Earnings, and Disability Compensation Among Veterans of the Iraq and Afghanistan Wars - Heaton, Paul (RAND Corporation, 2012)
This comprehensive, quantitative assessment of how injury sustained by service members deployed to Iraq and Afghanistan affects their subsequent labor market earnings also explores the extent to which retirement and disability payments compensate for any resulting earnings losses. The analysis controls for a rich array of individual-level characteristics, including labor market outcomes prior to deployment.